Arbuscular Mycorrhizal Fungal Hyphae Alter Soil Bacterial Community and Enhance Polychlorinated Biphenyls Dissipation - Qin, Hua; Brookes, Philip C.; Xu, Jianming (Frontiers in Microbiology, 2016)
We investigated the role of arbuscular mycorrhizal fungal (AMF) hyphae in alternation of soil microbial community and Aroclor 1242 dissipation. A two-compartment rhizobox system with double nylon meshes in the central was employed to exclude the influence of Cucurbita pepo L. root exudates on hyphal compartment soil. To assess the quantitative effect of AMF hyphae on soil microbial community, we separated the hyphal compartment soil into four horizontal layers from the central mesh to outer wall (e.g. L1-L4). Soil total PCBs dissipation rates ranged from 35.67% of L4 layer to 57.39% of L1 layer in AMF inoculated treatment, which were significant higher than the 17.31% of the control (P<0.05). The dissipation rates of tri-, tetrachlorinated biphenyls as well as the total PCBs were significantly correlated with soil hyphal length (P<0.01). Real-time quantitative PCR results indicated that the Rhodococcus-like bphC gene was 2-3 orders of magnitude more than that of Pseudomonas-like bphC gene, and was found responded positively to AMF. Phylogenetic analyses of the 16S rDNA sequenced by the Illumina Miseq sequencing platform indicated that AMF hyphae altered bacterial community compositions. The phylum Betaproteobacteria and Actinobacteria were dominated in the soil, while Burkholderials and Actinomycetales were dominated at the order level. Taxa from the Comamonadaceae responded positively to AMF and trichlorinated biphenyl dissipation, while taxa from the Oxalobacteraceae and Streptomycetaceae responded negatively to AMF and PCB congener dissipation. Our results suggested that the AMF hyphal exudates as well as the hyphae per se did have quantitative effects on shaping soil microbial community, and could modify the PCBs dissipation processes consequently.